Halal cultivated meat: an untapped opportunity - Attwood, Sophie; Jameel, Shahid; Fuseini, Awal; AlKhalawi, Eman; Hajat, Cother (Frontiers in Nutrition, 2023)
The global Halal food market is forecast to reach US$1.67 trillion by 2025, growing to meet the dietary demands of a rapidly increasing Muslim population, set to comprise 30% of the global population by mid-century. Meat consumption levels are increasing in many Muslim countries, with important implications for health and environmental sustainability. Alt protein products are currently being manufactured and positioned as one possible solution to reduce the environmental impact of meat consumption, yet, little is currently known about the Halal status of these products, nor the extent to which they appeal to Muslim consumers in emerging markets in Asia and Africa. Here, we explore key considerations regarding the acceptability of alt protein products for Muslim consumers, explore Halal certification requirements in the context of cultivated meat, and examine some unique beliefs within the Islamic faith that may support, as well as impede, widespread adoption of alt protein among the 2.8 billion Muslims of the future.